Talazoparib plus enzalutamide in metastatic castration-resistant prostate cancer: safety analyses from the randomized, placebo-controlled, phase III TALAPRO-2 study - Azad, Arun; Fizazi, Karim; Matsubara, Nobuaki; Saad, Fred; De Giorgi, Ugo; Joung, Jae Young; Fong, Peter C. C.; Jones, Robert J.; Zschäbitz, Stefanie; Oldenburg, Jan; Shore, Neal D.; Dunshee, Curtis; et al. (European journal of cancer, 2024)
Background - This detailed analysis further characterizes the safety profile of talazoparib plus enzalutamide in the ongoing randomized, phase III TALAPRO-2 study in patients with metastatic castration-resistant prostate cancer (mCRPC). In both the all-comers and homologous recombination repair (HRR)-deficient populations, talazoparib plus enzalutamide significantly improved radiographic progression-free survival compared with placebo plus enzalutamide. - Methods - The talazoparib plus enzalutamide safety populations in TALAPRO-2 included 398 patients from cohort 1 (all-comers, unselected for HRR gene alterations) and 198 patients from the combined HRR-deficient population (patients from the all-comers population with HRR gene alterations plus subsequently enrolled patients with HRR gene alterations; cohort 2). Patients received talazoparib 0.5 mg (0.35 mg, moderate renal impairment) and enzalutamide 160 mg once daily. Safety analyses evaluated common treatment-emergent adverse events (TEAE), their type, severity, timing, seriousness, and relationship to study treatment. - Results - In the all-comers (n = 398) and HRR-deficient populations (n = 198), all-cause grade 3/4 (G3/4) TEAEs with talazoparib plus enzalutamide were reported in 71.9 % and 66.2 % of patients, respectively. Most common G3/4 hematologic TEAEs were anemia (46.7 % and 40.9 %, respectively), neutropenia (18.3 % and 18.7 %), and thrombocytopenia (7.3 % and 7.1 %). Median time to event was 3.3 and 3.3 months for G3/4 anemia, 2.3 and 2.3 months for G3/4 neutropenia, and 2.3 and 1.5 months for G3/4 thrombocytopenia. Maximum hemoglobin reduction occurred after 13 and 15 weeks of treatment. 18.8 % and 10.1 % of patients discontinued talazoparib. TEAEs were managed with dose interruption (62.1 % and 57.6 %), reduction (52.8 % and 52.0 %), hematologic supportive care (13.1 % and 10.6 %), and packed red blood cell transfusions (39.2 % and 35.9 %). - Conclusion - Talazoparib plus enzalutamide had a generally manageable safety profile in patients with mCRPC within the all-comers and the HRR-deficient populations. - ClinicalTrials.gov Identifier - NCT03395197